Оковка турьего рога из Черной могилы в свете данных булгарской летописи XIII в. Гази-Барадж тарихы и мифологии булгар - Львова, З.А. (Степи Европы в эпоху средневековья, 2009)
The paper proposes a new interpretation of the image on a silver binding of a big Caucasian goat horn from the Chiornaia Mogila barrow of the end of the 10th - the early 11th century. The interpretation is based on the Bulgharian mythology preserved in the Tatar national holidays and on the text of the Russian translation of the Gazi Baraj Tarixi - the Bulgharian chronicle of the 13th century.